Method for manufacturing electrodes, electrodes, and their applications
Patent Information
- Application Number
- JP2025058809
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2026-10-14
Smart Images

Figure 2026166080000001_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a method for producing an electrode, an electrode, and uses thereof.
Background Art
[0002] Examples of electricity storage devices including electrodes include secondary batteries such as lithium ion secondary batteries. In recent years, this type of electricity storage device is suitably used, for example, as a power source for driving vehicles such as battery electric vehicles (BEVs), hybrid electric vehicles (HEVs), and plug-in hybrid electric vehicles (PHEVs).
[0003] Japanese Patent Laid-Open No. 2010-170972 discloses a positive electrode member for use in a non-aqueous electrolyte battery including a positive electrode, a negative electrode, and a non-aqueous electrolyte layer disposed between these electrodes. This positive electrode member includes a first active material layer containing a positive electrode active material, a second active material layer containing a positive electrode active material and disposed to face the first active material layer, and a positive electrode current collecting layer disposed between the first active material layer and the second active material layer. The first active material layer, the second active material layer, and the positive electrode current collecting layer are integrated by sintering. This publication states that such a configuration makes it possible to fabricate a non-aqueous electrolyte battery with a large capacity.
[0004] Japanese Patent Laid-Open No. 2015-220107 discloses an all-solid lithium ion secondary battery having a battery element body with an electrolyte layer between a positive electrode layer and a negative electrode layer, and electrodes at the ends of the battery element body. The battery element body is coated with a water vapor prevention layer made of an inorganic material with a thickness of 5 to 1000 nm. This publication states that with such a configuration, in an all-solid lithium ion secondary battery that can be surface-mounted on a printed circuit board, the reaction between the waterproof layer and the element body material of the all-solid lithium ion secondary battery can be suppressed, and the influence of water vapor can be suppressed.
[0005] The energy storage component disclosed in Japanese Patent Publication No. 2019-164957 comprises a substrate having an insulating main surface, a positive electrode active material layer formed on the main surface, a negative electrode active material layer formed on the main surface and facing the positive electrode active material layer, a positive electrode current collector layer formed on the main surface and adjacent to the positive electrode active material layer, and a negative electrode current collector layer formed on the main surface and adjacent to the negative electrode active material layer. The publication states that the electrodes can be made thinner with this configuration. [Prior art documents] [Patent Documents]
[0006] [Patent Document 1] Japanese Patent Publication No. 2010-170972 [Patent Document 2] Japanese Patent Publication No. 2015-220107 [Patent Document 3] Japanese Patent Publication No. 2019-164957 [Overview of the project] [Problems that the invention aims to solve]
[0007] The inventors of this invention aim to suppress a decrease in conductivity in an electrode comprising an electrode active material layer and a current collecting layer provided on the surface of the electrode active material layer. [Means for solving the problem]
[0008] The technology disclosed herein provides a method for manufacturing an electrode comprising an electrode active material layer containing an electrode active material and a resin binder, and a current collector layer provided on the surface of the electrode active material layer. This manufacturing method includes providing an electrode active material layer on the surface of a substrate, applying a slurry containing a first metal powder with an average particle size of less than 100 nm based on dynamic light scattering to the surface of the electrode active material layer provided on the substrate, and heat-treating the electrode active material layer and the slurry applied to the surface of the electrode active material layer at a temperature lower than the thermal decomposition temperature of the resin binder to provide a current collector layer on the surface of the electrode active material layer. This configuration makes it possible to suppress a decrease in the conductivity of the electrode.
[0009] From another perspective, the technology disclosed herein discloses a method for manufacturing an energy storage device including electrodes. This manufacturing method includes manufacturing electrodes using the electrode manufacturing method described above. This configuration makes it possible to suppress a decrease in the conductivity of the electrodes, and thus suppress a decrease in the performance of the energy storage device.
[0010] From another perspective, the technology disclosed herein discloses an electrode comprising an electrode active material layer containing an electrode active material and a resin binder, and a current collecting layer provided on the surface of the electrode active material layer. The current collecting layer includes metal particles having an average particle diameter of 100 nm to 10 μm based on electron microscope observation images of a cross-section along the thickness direction of the electrode active material layer, and metal bonding portions connecting the metal particles. This configuration makes it possible to suppress a decrease in the conductivity of the electrode.
[0011] From another perspective, the technology disclosed herein discloses an energy storage device including the electrodes described above. This configuration suppresses the degradation of the electrode conductivity, thereby suppressing the performance degradation of the energy storage device. [Brief explanation of the drawing]
[0012] [Figure 1] Figure 1 is a flowchart of the manufacturing process. [Figure 2] Figure 2 is a cross-sectional view of the substrate S and the positive electrode 32. [Figure 3] Figure 3 is a plan view of the positive electrode active material layer 32a and the positive electrode current collector layer 32b. [Figure 4] Figure 4 is a perspective view of the energy storage device 1. [Figure 5] Figure 5 is a perspective view of the energy storage device 1. [Figure 6] Figure 6 is a cross-sectional view taken along the line VI-VI in Figure 4. [Figure 7] Figure 7 is a schematic cross-sectional view of the electrode body 30. [Figure 8] Figure 8 is a cross-sectional view of the positive electrode 232. [Modes for carrying out the invention]
[0013] An embodiment of the energy storage device disclosed herein is described below. The embodiment described herein is not limited to the technology disclosed herein. Unless otherwise specified, the technology disclosed herein is not limited to the embodiment described herein. The drawings are schematic and do not necessarily reflect the actual objects. Components and parts that perform the same function are appropriately denoted by the same reference numerals, and redundant explanations may be omitted. The reference numerals "X", "Y", and "Z" in the drawings indicate the "first direction", "second direction", and "third direction" in this specification, respectively. The reference numerals "X1", "X2", "Y1", "Y2", "Z1", and "Z2" in the drawings indicate the orientation in the drawings. However, these directions are defined for the convenience of explanation and do not limit the installation method of the energy storage device in any way. The notation "A~B" indicating a numerical range means "A or more and B or less" unless otherwise specified, and also includes the meaning of "greater than A and less than B".
[0014] In this specification, "energy storage device" refers to a device in which charging and discharging occur through the movement of a charge carrier between a pair of electrodes (positive electrode and negative electrode) via an electrolyte. Energy storage devices include secondary batteries such as lithium-ion secondary batteries, nickel-metal hydride batteries, and nickel-cadmium batteries. An energy storage device may be, for example, a lithium-ion secondary battery.
[0015] <First Embodiment> Figure 1 is a flowchart of the manufacturing method. Figure 1 shows the flow of a method for manufacturing an electrode according to one embodiment. Figure 2 is a cross-sectional view of the substrate S and the positive electrode 32. Figure 2 schematically shows the cross-sectional structure along the thickness direction of the positive electrode 32 provided on the surface of the substrate S. In this embodiment, the "thickness direction of the positive electrode 32" refers to the lamination direction of the positive electrode active material layer 32a and the positive electrode current collector layer 32b. Hereinafter, as an example of the method for manufacturing an electrode disclosed herein, the method for manufacturing the positive electrode 32 will be described with appropriate reference to Figure 1 and Figure 2. Although not particularly limited, in the following description, the positive electrode 32 is a positive electrode of a lithium ion secondary battery.
[0016] As shown in Figure 1, the manufacturing method includes a preparation step S1, a first application step S2, a first drying step S3, a second application step S4, a heat treatment step S5, a third application step S6, a second drying step S7, and a separation step S8.
[0017] In the preparation step S1, for example, a first slurry and a second slurry are prepared. Here, the first slurry is a slurry for forming an active material layer, and includes a material for forming the positive electrode active material layer 32a. The first slurry contains, for example, a positive electrode active material, a resin binder, a conductive material, and a solvent.
[0018] As the positive electrode active material, for example, various positive electrode active materials used in lithium ion secondary batteries can be used without particular limitation. The positive electrode active material may be, for example, a lithium composite oxide, a lithium transition metal phosphate compound, or the like. The crystal structure of the positive electrode active material is not particularly limited, and may be a layered structure, a spinel structure, an olivine structure, or the like. The positive electrode active material may contain one type alone, or may contain two or more types.
[0019] As lithium composite oxides, lithium transition metal composite oxides containing at least one of Ni, Co, and Mn as a transition metal element are preferred. For example, lithium nickel-based composite oxides, lithium cobalt-based composite oxides, lithium manganese-based composite oxides, lithium nickel-manganese-based composite oxides, lithium nickel-cobalt-manganese-based composite oxides, lithium nickel-cobalt-aluminum-based composite oxides, lithium iron-nickel-manganese-based composite oxides, and the like can be preferably used.
[0020] In this specification, "lithium nickel cobalt manganese composite oxide" is a term that encompasses oxides containing not only Li, Ni, Co, Mn, and O as constituent elements, but also one or more additive elements other than those listed above. Examples of such additive elements include transition metal elements and main group metal elements such as Mg, Ca, Al, Ti, V, Cr, Y, Zr, Nb, Mo, Hf, Ta, W, Na, Fe, Zn, and Sn. Additive elements may also be metalloid elements such as B, C, Si, and P; or nonmetallic elements such as S, F, Cl, Br, and I. This also applies to the lithium nickel composite oxide, lithium cobalt composite oxide, lithium manganese composite oxide, lithium nickel manganese composite oxide, lithium nickel cobalt aluminum composite oxide, lithium iron nickel manganese composite oxide, etc.
[0021] Examples of lithium transition metal phosphate compounds include lithium iron phosphate (LiFePO4), lithium manganese phosphate (LiMnPO4), and lithium manganese iron phosphate.
[0022] The resin binder may include, for example, polyvinylidene fluoride (PVdF), PTFE (polytetrafluoroethylene), SBR (styrene-butadiene rubber), etc. As the conductive material, for example, carbon black such as acetylene black (AB); carbon fibers such as vapor-processed carbon fiber (VGCF) and carbon nanotubes (CNT); other carbon materials such as graphite; etc. As the solvent, for example, N-methylpyrrolidone may be used.
[0023] When the total solid components of the first slurry are considered to be 100% by mass, the content of the positive electrode active material is, for example, 80% to 99.5% by mass, with 90% to 99% by mass being preferred. When the total solid components of the first slurry are considered to be 100% by mass, the content of the conductive material is, for example, 0.1% to 20% by mass, with 0.3% to 15% by mass being preferred. When the total solid components of the first slurry are considered to be 100% by mass, the content of the binder is, for example, 0.4% to 15% by mass, with 0.5% to 10% by mass being preferred. The solid components of the first slurry here include the positive electrode active material, resin binder, conductive material, and other additives as needed. When the total solid components of the first slurry are considered to be 100% by mass, the content of the solid components is generally 50% to 90% by mass, and can be appropriately set considering ease of application, ease of drying, etc.
[0024] The second slurry, in this case, is a slurry for forming the current collector layer and contains materials for forming the positive electrode current collector layer 32b. The second slurry includes, for example, the first metal powder, a surfactant, and a solvent.
[0025] The first metal powder may be composed of a metal that does not dissolve at the positive electrode potential when using an energy storage device including the positive electrode 32. For example, gold powder, silver powder, aluminum powder, etc., can be preferably used as the first metal powder.
[0026] The average particle size of the first metal powder is less than 100 nm. From the viewpoint of better realizing the effects of the technology disclosed herein, the average particle size of the first metal powder may be, for example, 1 nm to 90 nm, preferably 5 nm to 80 nm, more preferably 10 nm to 70 nm, even more preferably 15 nm to 60 nm, and particularly preferably 20 nm to 50 nm. In this specification, the average particle size of the first metal powder is the average particle size (D) based on the dynamic light scattering method (DLS method). DLS ) is the average particle diameter (D) based on the DLS method. DLS ) can be measured in accordance with JIS Z 8828:2013. In such measurements, commercially available measuring devices such as the "Zetasizer Nano ZS" measuring device manufactured by Malvern Panalytical can be used.
[0027] The shape of the first metal particles constituting the first metal powder is not particularly limited and may be spherical, plate-shaped, columnar, needle-shaped, flake-shaped, etc.
[0028] As a surfactant, any surfactant used in this type of application can be used without particular limitations. For example, acrylic acid polymers can be preferably used as surfactants. Acrylic acid polymers may be polymers of at least one of the following: acrylic acid monomer, methacrylic acid monomer, acrylic acid ester monomer, and methacrylic acid ester monomer. As a solvent, any solvent used in this type of application can be used without particular limitations. For example, alcohols such as decanol and terpineol can be preferably used as solvents.
[0029] When the entire second slurry is considered to be 100% by mass, the content of the first metal powder may be approximately 50% to 90% by mass. In the second slurry, the content of the surfactant and the content of the solvent are not particularly limited and can be set as appropriate. The second slurry may also contain additives other than those described above, as long as they do not hinder the effects of the technology disclosed herein, and may contain additives used in this type of application. Examples of such additives include resin binders. The resin binder may be the same as the resin binder contained in the first slurry, and may also contain celluloses such as ethylcellulose and carboxymethylcellulose; epoxy resins; acrylic resins; etc.
[0030] The method for preparing the first slurry and the second slurry is not particularly limited and may be a conventionally known method. For example, the first slurry and the second slurry may be prepared by mixing the materials using a commercially available mixing device or the like.
[0031] In the first application step S2, for example, the first slurry is applied to the surface of the substrate S. By performing the first application step S2, for example, a coating film of the first slurry is obtained on the substrate S. The method of applying the first slurry is not particularly limited, and methods used in this type of application can be used as appropriate. For example, the first slurry can be applied (coated) to the surface of the substrate S by using a coating device such as a gravure coater, comma coater, slit coater, or die coater. As the substrate S, for example, a release-type substrate used in this type of application can be used without particular limitation. As a release-type substrate, there are no particular limitations, but examples include a ceramic substrate, a substrate with a silicone resin, fluororesin, etc. on its surface, etc.
[0032] In the first drying step S3, for example, the substrate S and the first slurry applied to the substrate S (in this case, the coating film of the first slurry) are subjected to a drying treatment. By performing the first drying step S3, for example, the solvent can be removed from the first slurry, and a positive electrode active material layer 32a, which is a dried film of the first slurry, is obtained on the substrate S. The first drying step S3 may be performed by using a drying apparatus such as a drying oven. The drying temperature and drying time can be set appropriately according to the content ratio of solid components in the first slurry, etc. The drying temperature may be, for example, 60 to 200 degrees (preferably 70 to 150 degrees). The drying time may be, for example, 10 seconds to 30 minutes (preferably 30 seconds to 10 minutes).
[0033] In the second application step S4, for example, the second slurry is applied to the surface of the positive electrode active material layer 32a provided on the substrate S after the first drying step S3. By performing the second application step S4, for example, a coating film of the second slurry is obtained on the surface of the positive electrode active material layer 32a. The method of applying the second slurry is not particularly limited, and a method used in this type of application may be used as appropriate. In this embodiment, printing methods such as screen printing and inkjet printing are preferably used. Alternatively, the second slurry may be printed on transfer paper in a predetermined pattern and then transferred to the surface of the positive electrode active material layer 32a.
[0034] In this embodiment, in the second application step S4, the second slurry is applied (in this case, printed) to the surface of the positive electrode active material layer 32a in a mesh shape. As a result, after the heat treatment step S5 described later, a positive electrode current collector layer 32b with a mesh shape in plan view is obtained (see Figure 3). Figure 3 is a plan view of the positive electrode active material layer 32a and the positive electrode current collector layer 32b. Figure 3 shows a plan view of the positive electrode active material layer 32a and the positive electrode current collector layer 32b from above after the heat treatment step S5 described later.
[0035] In the heat treatment step S5, for example, after the second application step S4, the positive electrode active material layer 32a and the second slurry applied to the surface of the positive electrode active material layer 32a are heat-treated. By performing the heat treatment step S5, for example, the solvent can be removed from the second slurry and the first metal particles can be sintered together, resulting in a positive electrode current collector layer 32b, which is a fired film of the second slurry, on the positive electrode active material layer 32a. The heat treatment step S5 may be performed, for example, by using a heat treatment device such as a firing furnace. The temperature and time of the heat treatment should be appropriately set according to the content ratio of solid components in the second slurry, the average particle size of the first metal powder, the type of solvent contained in the second slurry, the type of resin binder contained in the positive electrode active material layer 32a, etc. The heat treatment temperature is lower than the thermal decomposition temperature of the resin binder contained in the positive electrode active material layer 32a. From the viewpoint of preventing thermal decomposition of the resin binder, the heat treatment temperature is preferably 200 degrees Celsius or lower, more preferably 190 degrees Celsius or lower, and even more preferably 180 degrees Celsius or lower. On the other hand, from the viewpoint of improving the sinterability of the first metal powder, the heat treatment temperature is, for example, 100 degrees Celsius or higher, preferably 110 degrees Celsius or higher, and more preferably 120 degrees Celsius or higher. The heat treatment time is, for example, 15 minutes to 10 hours, and preferably 30 minutes to 5 hours.
[0036] In the third application step S6, for example, after the heat treatment step S5, the first slurry is applied to the surface of the positive electrode current collector layer 32b. By performing the third application step S6, for example, a coating film of the first slurry is obtained on the positive electrode current collector layer 32b. The method of applying the first slurry may be the same as the method used in the first application step S2.
[0037] The second drying step S7 involves drying the first slurry (in this case, the coating film of the first slurry) applied to the surface of the positive electrode current collector layer 32b after the third application step S6. By performing the second drying step S7, for example, the solvent can be removed from the first slurry, and a positive electrode active material layer 32a, which is a dried film of the first slurry, is obtained on the positive electrode current collector layer 32b. Furthermore, by performing this step, a laminate of the positive electrode active material layer 32a and the positive electrode current collector layer 32b is obtained on the substrate S. The second drying step S7 may be performed using the same method as the method used in the first drying step S3. The drying temperature and drying time in this step may be the same as the drying temperature and drying time in the first drying step S3.
[0038] In the separation step S8, for example, after the second drying step S7, the laminate of the positive electrode active material layer 32a and the positive electrode current collector layer 32b is separated from the substrate S. This yields the positive electrode 32.
[0039] The above describes an example of an electrode manufacturing method disclosed herein. However, the steps described above may be omitted as appropriate, and other steps may be added as appropriate, as long as the effects of the disclosed technology can be obtained. For example, a pressing step may be performed after the first drying step S3 and / or the second drying step S7. By performing the pressing step, the positive electrode active material layer 32a can be compressed to a desired density, and the positive electrode active material can be densely packed. The pressing step can be performed, for example, by using a conventionally known pressing device such as a roller press. Alternatively, for example, the third application step S6 and the second drying step S7 may be omitted as appropriate, depending on the desired laminated structure of the positive electrode 32.
[0040] The above-described manufacturing method is a method for manufacturing a positive electrode 32 comprising a positive electrode active material layer 32a containing a positive electrode active material and a resin binder, and a positive electrode current collector layer 32b provided on the surface of the positive electrode active material layer 32a. This manufacturing method includes providing a positive electrode active material layer 32a on the surface of a substrate S, applying a slurry (here, a second slurry) containing a first metal powder with an average particle size of less than 100 nm based on the DLS method to the surface of the positive electrode active material layer 32a provided on the substrate S, and heat-treating the positive electrode active material layer 32a and the second slurry applied to the surface of the positive electrode active material layer 32a at a temperature lower than the thermal decomposition temperature of the resin binder to provide a positive electrode current collector layer 32b on the surface of the positive electrode active material layer 32a.
[0041] In other words, in this manufacturing method, a positive electrode active material layer 32a is provided on the surface of a substrate S, and a second slurry containing a first metal powder is applied to the surface of the positive electrode active material layer 32a and heat-treated to provide a positive electrode current collector layer 32b on the surface of the positive electrode active material layer 32a. Here, the average particle size of the first metal powder used to form the positive electrode current collector layer 32b is less than 100 nm. This makes it possible to lower the sintering temperature of the first metal particles constituting the first metal powder. Therefore, the heat treatment for forming the positive electrode current collector layer 32b can be carried out at a temperature lower than the thermal decomposition temperature of the resin binder contained in the positive electrode active material layer 32a. This heat treatment makes it possible to suppress the burning out of the resin binder contained in the positive electrode active material layer 32a. Therefore, it is possible to suppress the weakening of the bonding between the positive electrode active materials in the positive electrode active material layer 32a, and consequently, to suppress the decrease in the conductivity of the positive electrode 32.
[0042] The heat treatment temperature may be 200 degrees Celsius or lower. This can better reduce the risk of thermal decomposition of the resin binder contained in the positive electrode active material layer 32a.
[0043] The resin binder contained in the positive electrode active material layer 32a may be PVdF. This allows for more appropriate bonding of the positive electrode active materials within the positive electrode active material layer 32a.
[0044] In applying the second slurry, the second slurry may be applied to the surface of the positive electrode active material layer 32a in a mesh shape when viewed from above. This reduces the amount of first metal powder used to form the positive electrode current collector layer 32b. As a result, for example, the amount of heat generated during an internal short circuit can be reduced. Furthermore, the energy storage device 1 (see Figure 4, etc.) can be made smaller or lighter. When the total area of the surface on which the positive electrode current collector layer 32b is provided on the positive electrode active material layer 32a is taken as 100%, the area of the positive electrode current collector layer 32b is preferably about 10% to 90%. The thickness of the positive electrode current collector layer 32b is, for example, 0.5 μm to 20 μm, and preferably 1 μm to 10 μm.
[0045] As described above, the electrode manufacturing method disclosed herein may also be a method for manufacturing the positive electrode 32. This makes it possible to provide a positive electrode in which the decrease in conductivity is suppressed. Furthermore, since the amount of metal required to form the current collector layer can be reduced compared to a conventional positive electrode with current collector foil, it is possible to provide a safer positive electrode and realize a smaller or lighter energy storage device.
[0046] The first metal powder may be gold powder or silver powder. Gold powder and silver powder have excellent handling properties, for example. This can increase the productivity of the positive electrode 32. Furthermore, gold powder and silver powder have excellent electrical conductivity. This can increase the conductivity of the positive electrode 32.
[0047] The method for manufacturing the positive electrode 32 described above may be included, for example, in the method for manufacturing the energy storage device 1 (see Figure 4). Figures 4 and 5 are perspective views of the energy storage device 1. Figure 4 shows the energy storage device 1 with the Z1 side as the upper side in the drawing. In Figure 4, the top surface 12 of the energy storage device 1 is positioned at the top of the drawing. Figure 5 shows the energy storage device 1 with the Z2 side as the upper side in the drawing. In Figure 5, the bottom surface 11 of the energy storage device 1 is positioned at the top of the drawing. Figure 6 is a cross-sectional view taken along line VI-VI in Figure 4. Figure 6 shows the cross-sectional structure of the energy storage device 1 with one of the first side surfaces 13a (see Figure 1) positioned as the front.
[0048] As shown in Figures 4 to 6, the energy storage device 1 comprises a case 10, a positive electrode terminal 22, a negative electrode terminal 24, an electrode body 30, a spacer 40, a resin film 50, and an electrolyte (not shown). In this case, the energy storage device 1 is a lithium-ion secondary battery.
[0049] As shown in Figures 4 to 6, case 10 has a bottom surface 11, a top surface 12, a pair of opposing first sides 13a, 13b, and a pair of opposing second sides 14a, 14b. Case 10 is hexahedral in this case. In this embodiment, the bottom surface 11 and the top surface 12 are rectangular and face each other. In the configurations shown in Figures 4 and 5, the pair of opposing first sides 13a, 13b extend from a pair of opposing long sides 11a on the bottom surface 11 and have a relatively large area. The pair of opposing second sides 14a, 14b extend from a pair of opposing short sides 11b on the bottom surface 11 and have a relatively small area.
[0050] As shown in Figures 4 to 6, the case 10 comprises a case body 10A, a first sealing plate 10B, and a second sealing plate 10C. The case body 10A is, for example, rectangular and has a bottom surface 11, a top surface 12, and a pair of opposing first sides 13a and 13b. In this embodiment, the portion of the case body 10A enclosed by the bottom surface 11, the top surface 12, and the pair of opposing first sides 13a and 13b is an opening. As shown in Figure 6, the energy storage device 1 has two openings 15a and 15b.
[0051] The case body 10A can be manufactured, for example, by bending a single metal plate into a cylindrical shape and joining the joint (for example, by welding). Therefore, as shown in Figure 4, the case body 10A has a joint portion 16 extending along the first direction X on its upper surface 12. The case body 10A is not particularly limited, but it may be made of a metal such as aluminum, aluminum alloy, iron, or iron alloy.
[0052] As shown in Figure 5, the case body 10A has a safety valve 17 on its bottom surface 11. The safety valve 17 is a thin-walled section designed to rupture and release the internal pressure when the internal pressure of the case 10 reaches a predetermined value. The safety valve 17 does not necessarily have to be provided on the bottom surface 11. In other embodiments, the safety valve 17 may be provided on the top surface 12 or the first side surfaces 13a, 13b.
[0053] The first sealing plate 10B is, for example, a member that seals one of the openings 15a. The first sealing plate 10B is, for example, a substantially rectangular plate-shaped member. In this embodiment, the first sealing plate 10B is fitted into one of the openings 15a and joined by welding (for example, laser welding). As shown in Figures 4 and 6, a positive terminal 22 is attached to the first sealing plate 10B.
[0054] In this embodiment, the first sealing plate 10B has an electrolyte injection section 19. The electrolyte injection section 19 has an electrolyte injection hole 19A and a sealing plug 19B. The electrolyte injection hole 19A is, in this case, the part where electrolyte is injected into the case 10 during the manufacturing process of the energy storage device 1. In this embodiment, the electrolyte injection hole 19A is provided on the first sealing plate 10B, close to the upper surface 12. The sealing plug 19B is, in this case, a member that closes the electrolyte injection hole 19A.
[0055] The second sealing plate 10C is, for example, a member that seals the other opening 15b. The second sealing plate 10C is, for example, a substantially rectangular plate-shaped member. In this embodiment, the second sealing plate 10C is fitted into the other opening 15b and joined by welding (for example, laser welding). As shown in Figures 5 and 6, the negative electrode terminal 24 is attached to the second sealing plate 10C.
[0056] In the configurations shown in Figures 4 to 6, the first sealing plate 10B and the second sealing plate 10C constitute a pair of opposing second sides 14a and 14b. Preferably, both the first sealing plate 10B and the second sealing plate 10C are made of the same metal material as the metal material that constitutes the case body 10A.
[0057] The positive electrode terminal 22 is electrically connected to, for example, the positive electrode 32 of the electrode body 30 (see Figure 7). As shown in Figures 4 and 6, the positive electrode terminal 22 is attached to the first sealing plate 10B. As shown in Figure 6, the positive electrode terminal 22 is electrically connected to the positive electrode tab 33 of the electrode body 30 via the positive electrode current collector 23. The positive electrode terminal 22 is made of, for example, metal, preferably aluminum or an aluminum alloy. The positive electrode terminal 22 may also constitute the positive electrode current collector 23.
[0058] The negative electrode terminal 24 is electrically connected to, for example, the negative electrode 34 of the electrode body 30 (see Figure 7). As shown in Figures 5 and 6, the negative electrode terminal 24 is attached to the second sealing plate 10C. As shown in Figure 6, the negative electrode terminal 24 is electrically connected to the negative electrode tab 35 of the electrode body 30 via the negative electrode current collector 25. The negative electrode terminal 24 is made of, for example, metal, preferably copper or a copper alloy. The negative electrode terminal 24 may also constitute the negative electrode current collector 25.
[0059] The electrode body 30 is, for example, a power generation element in the energy storage device 1. As shown in Figure 6, the electrode body 30 is housed in the case 10. Figure 7 is a schematic cross-sectional view of the electrode body 30. Figure 7 schematically shows the cross-sectional structure of the electrode body 30 as seen from the side of the first sealing plate 10B (see Figure 6). The electrode body 30 is, for example, flattened. As shown in Figures 6 and 7, the electrode body 30 has a pair of opposing first end faces 30A1, 30A2 and a pair of opposing second end faces 30B1, 30B2. In this embodiment, the first end faces 30A1, 30A2 are the laminated surfaces of the electrode and the separator 36 and are open surfaces that open outwards from the electrode body 30. As shown in Figure 6, the first end face 30A1 faces the first sealing plate 10B. The first end face 30A2 faces the second sealing plate 10C. In this embodiment, the second end faces 30B1 and 30B2 are formed by separators 36. Therefore, the separators 36 that make up the second end faces 30B1 and 30B2 constitute the outer surface of the electrode body 30. The second end faces 30B1 and 30B2 are rectangular in shape and face the first side surfaces 13a and 13b of the case 10.
[0060] In the configuration shown in Figure 6, one first end face 30A1 has a positive electrode tab 33 connected to the positive electrode 32 of the electrode body 30. The other first end face 30A2 has a negative electrode tab 35 connected to the negative electrode 34 of the electrode body 30. The positive electrode tabs 33 are provided on each positive electrode 32 included in the electrode body 30. The positive electrode tabs 33 provided on each positive electrode 32 (multiple positive electrode tabs 33) can be stacked, for example, to form a group of positive electrode tabs. The negative electrode tabs 35 are provided on each negative electrode 34 included in the electrode body 30. The negative electrode tabs 35 provided on each negative electrode 34 (multiple negative electrode tabs 35) can be stacked, for example, to form a group of negative electrode tabs.
[0061] As shown in Figure 7, the electrode body 30 comprises a positive electrode 32, a negative electrode 34, and a separator 36 interposed between the positive electrode 32 and the negative electrode 34. In this embodiment, the electrode body 30 is a flat electrode body with a zigzag structure in which a long strip-shaped separator 36 is folded alternately at predetermined intervals, and a plurality of positive electrodes 32 and a plurality of negative electrodes 34 are alternately sandwiched between the zigzag separator 36. In the configuration shown in Figure 7, the separator 36 is wrapped around the outermost circumference of the zigzag structure and constitutes the outer surface of the electrode body 30. In this embodiment, the separator 36 is wrapped around the outermost electrode (in this embodiment, the negative electrode 34 (see Figure 7)) within the electrode body 30 at least once. Tape 39 is attached to the end portion 36e of the separator 36 to prevent loosening of the electrode body 30.
[0062] The positive electrode 32 may be, for example, a rectangular sheet-shaped positive electrode sheet. In this embodiment, a positive electrode 32 manufactured using the manufacturing method described above is used. The positive electrode 32 is provided with a positive electrode tab 33. The positive electrode tab 33 is not particularly limited and may be, for example, a metal foil. The positive electrode tab 33 may be a metal foil made of, for example, gold, silver, aluminum, or an alloy thereof. The positive electrode tab 33 may be attached, for example, so that a part of it is in contact with the positive electrode current collector layer 32b.
[0063] The negative electrode 34 may be, for example, a rectangular sheet-shaped negative electrode sheet. In this embodiment, the negative electrode 34 comprises a rectangular sheet-shaped negative electrode current collector foil and a negative electrode active material layer provided on the surface of the negative electrode current collector foil. The negative electrode current collector foil is preferably made of, for example, copper or a copper alloy. In the embodiment shown in Figure 6, a negative electrode tab 35 is provided at the end of the negative electrode current collector foil (the end on the X2 side in the figure). The negative electrode tab 35 has, for example, an exposed region where the negative electrode current collector foil is exposed. The exposed portion of the negative electrode tab 35 is joined to, for example, the negative electrode current collector portion 25. The negative electrode active material layer contains, for example, a negative electrode active material. The negative electrode active material is, for example, a material that can reversibly absorb and release charge carriers. As the negative electrode active material, for example, a material used as the negative electrode active material for this type of energy storage device can be used without particular limitation. The negative electrode active material layer may contain components other than the negative electrode active material (e.g., binder, thickener, dispersant, etc.).
[0064] As the separator 36, for example, a separator from this type of energy storage device can be used without particular limitation. The separator 36 may be a single-layer structure, or it may be a structure of two or more layers with different properties and characteristics (thickness, porosity, etc.), for example, a three-layer structure. The separator 36 is made of resin, for example, and is preferably made of polyolefin resin. The polyolefin resin may be polyethylene, polypropylene, or a mixture thereof.
[0065] As the electrolyte, for example, the electrolyte used in this type of energy storage device can be used without particular limitation. The electrolyte is, for example, a non-aqueous electrolyte containing a non-aqueous solvent (organic solvent) and a supporting salt. Examples of non-aqueous solvents include carbonates such as ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate. Examples of supporting salts include fluorine-containing lithium salts such as lithium hexafluoride phosphate (LiPF6).
[0066] The spacer 40 is a component that is placed, for example, between the case 10 and the electrode body 30. In the configuration shown in Figure 6, the spacer 40 is placed between the case 10 and the first end faces 30A1 and 30A2 of the electrode body 30. As shown in Figure 6, the spacer 40 is placed between the first sealing plate 10B and the electrode body 30 (first end face 30A1 on the X1 side), and between the second sealing plate 10C and the electrode body 30 (first end face 30A2 on the X2 side). The spacer 40 may be made of an insulating resin (for example, polyamide resin, etc.) that has been conventionally used in this type of energy storage device.
[0067] The resin film 50 is, for example, a component that insulates the case 10 from the electrode body 30. As shown in Figure 6, the resin film 50 is arranged to surround the outer circumference of the electrode body 30. In this embodiment, the resin film 50 is cylindrical and houses the electrode body 30 inside. As the resin material constituting the resin film 50, for example, the resin material constituting the resin film included in this type of energy storage device may be used. Such resin materials may be, for example, polyamide resin, polyolefin resin (polyethylene, polypropylene, etc.).
[0068] The energy storage device 1 can be used for various purposes, but it is particularly suitable for use as a power source (driving power supply) for motors mounted on vehicles such as passenger cars and trucks. The type of vehicle is not particularly limited, but preferred examples include plug-in hybrid vehicles (PHEVs), hybrid electric vehicles (HEVs), and battery electric vehicles (BEVs).
[0069] While embodiments of the technology disclosed herein have been described above, these embodiments are merely illustrative and do not limit the scope of the claims. The technology described in the claims includes, for example, various modifications and changes to the above embodiments.
[0070] <Second Embodiment> The second slurry may further contain a second metal powder different from the first metal powder. The average particle size of the second metal powder is 100 nm to 10 μm. This allows for a reduction in the proportion of the first metal powder in the second slurry. This reduces manufacturing costs and increases productivity. Regarding the metal powder contained in the second slurry, the ratio of the first metal powder to the second metal powder, when the total metal powder is considered to be 100% by mass, is preferably 1:99 to 50:50 by mass. If the mass ratio of the first metal powder in the metal powder exceeds 50% by mass, the cost reduction effect becomes difficult to obtain. On the other hand, if the mass ratio of the first metal powder in the metal powder is less than 1% by mass, it becomes difficult to efficiently conduct electricity through the second metal powder. When observing the current collector layer using SEM imagery after low-temperature sintering with a mixing ratio of, for example, 3:97 for the mass ratio of the first metal powder to the mass ratio of the second metal powder, the cross-sectional area originating from the first metal powder accounts for approximately 1% to 5% of the total cross-sectional area of the metal powder. The variation in cross-sectional area ratio observed by SEM imagery is due to the observation of a three-dimensional structure in which the first metal powder melts and fuses between the particles of the second metal powder, in two dimensions (SEM imagery). By observing about 10 images and taking the average value, the variation in cross-sectional area ratio can be suppressed.
[0071] From the viewpoint of reducing the content of the first metal powder in the second slurry, the average particle size of the second metal powder is preferably 200 nm or more, and more preferably 300 nm or more. On the other hand, from the viewpoint of suppressing the thickness of the current collector layer from becoming too large, and thereby suppressing the reduction of volume energy density, the average particle size of the second metal powder is, for example, 8 μm or less, preferably 5 μm or less, and more preferably 3 μm or less. In this specification, the average particle size of the second metal powder is the particle size (D) corresponding to the cumulative frequency of 50% by volume from the fine particle side in the volume-based particle size distribution based on the laser diffraction-scattering method. 50 This refers to the average particle diameter (D) based on laser diffraction and scattering methods. 50For measuring the diameter, commercially available measuring devices such as the "SALD-2200" manufactured by Shimadzu Corporation can be used.
[0072] The shape of the second metal particles constituting the second metal powder may be, for example, spherical, plate-shaped, columnar, needle-shaped, or flake-shaped, but flake-shaped is preferred. By having the second metal particles in a flake shape, both the conductivity in the thickness direction of the electrode and the conductivity in the plane direction of the electrode can be further enhanced.
[0073] From the viewpoint of better realizing the effects of the technology disclosed herein, it is preferable that the first metal powder and the second metal powder are of the same type of metal. The second metal powder may be, for example, gold powder, silver powder, or aluminum powder.
[0074] Using the second slurry in this embodiment, the positive electrode 232 shown in Figure 8 can be manufactured. Figure 8 is a cross-sectional view of the positive electrode 232. Figure 8 schematically shows the cross-sectional structure of the positive electrode 232 in the thickness direction. Figure 8 further shows a partially enlarged cross-sectional view of the positive electrode current collector layer 232b. As shown in Figure 8, the positive electrode 232 comprises a positive electrode active material layer 232a and a positive electrode current collector layer 232b provided on the surface of the positive electrode active material layer 232a. The positive electrode active material layer 232a may be the same as the positive electrode active material layer 32a in the first embodiment.
[0075] As shown in Figure 8, the positive electrode current collector layer 232b includes metal particles 91 and a metal bonding portion 92. The average particle diameter of the metal particles 91 is 100 nm to 10 μm. From the viewpoint of better improving the conductivity of the positive electrode 232, the average particle diameter of the metal particles 91 is preferably 200 nm or more, and more preferably 300 nm or more. On the other hand, from the viewpoint of better improving the energy density in the positive electrode 232, the average particle diameter of the metal particles 91 is, for example, 8 μm or less, preferably 5 μm or less, and more preferably 3 μm or less. The average particle diameter of the metal particles 91 is the average particle diameter based on an electron microscope (SEM) observation image of a cross-section along the thickness direction of the positive electrode active material layer 232a. The average particle diameter of the metal particles 91 can be obtained, for example, by randomly selecting 10 or more metal particles 91 from a cross-sectional SEM observation image of the positive electrode active material layer 232a, measuring their equivalent circular diameters, and calculating the average value. In obtaining the average particle size of the metal particles 91, commercially available image analysis software may be used as appropriate.
[0076] The metal particles 91 here originate from the second metal powder contained in the second slurry. The shape of the metal particles 91 may be the same as that of the second metal particles. In the morphology shown in Figure 8, the metal particles 91 are flake-shaped. Here, the metal particles 91 are the same metal as the second metal powder.
[0077] The metallic bonding portion 92 here binds the metal particles 91 together. In the configuration shown in Figure 8, the metallic bonding portion 92 is molten metal. Here, the metallic bonding portion 92 originates from the first metal powder. In the heat treatment step S5 (see Figure 1), the first metal powder melts and binds the metal particles 91 (in this case, the second metal particles) together. Here, the metallic bonding portion 92 is the same metal as the first metal powder.
[0078] As shown in Figure 8, the positive electrode current collector layer 232b has a gap 232s. The gap 232s is surrounded by metal particles 91 and a metal bonding portion 92.
[0079] As described above, the positive electrode 232 comprises a positive electrode active material layer 232a containing a positive electrode active material and a resin binder, and a positive electrode current collector layer 232b provided on the surface of the positive electrode active material layer 232a. The positive electrode current collector layer 232b includes metal particles 91 and metal bonding portions 92. The average particle diameter of the metal particles 91 is 100 nm to 10 μm. The metal bonding portions 92 bond the metal particles 91 together.
[0080] In other words, in the positive electrode current collector layer 232b of the positive electrode 232, the metal particles 91 are cross-linked by the metal bonding portion 92. This makes it possible to further enhance the electrical conductivity between the metal particles 91 and suppress the decrease in the conductivity of the positive electrode 232.
[0081] The metal bonding portion 92 may be molten metal. This increases the contact area between the metal particles 91 and the metal bonding portion 92, thereby improving the bonding between the metal particles 91. This further enhances the effects described above.
[0082] The positive electrode current collector layer 232b may include air gaps 232s. This improves the permeability of the positive electrode current collector layer 232b, allowing gases generated during the manufacture or use of the positive electrode 232 to be better discharged from the positive electrode current collector layer 232b to the outside. This further enhances the safety of the energy storage device including the positive electrode 232.
[0083] The metal particles 91 may be in flake form. The flake-shaped metal particles 91 can be oriented along the planar direction of the positive electrode active material layer 232a in the positive electrode current collector layer 232b. This makes it possible to improve both the conductivity in the thickness direction and the conductivity in the planar direction of the positive electrode 232.
[0084] The metal particles 91 and the metal bonding portion 92 may be made of the same metal. This reduces the resistance between the metal particles 91 and the metal bonding portion 92, thereby better suppressing the decrease in conductivity of the positive electrode 232.
[0085] The metal particles 91 and the metal bonding portion 92 may be made of gold or silver. This allows for better realization of the effects of the technology disclosed herein.
[0086] The energy storage device 1 may include a positive electrode 232 in place of, or together with, the positive electrode 32. As described above, the positive electrode 232 reduces the decrease in conductivity, thus improving the performance of the energy storage device 1.
[0087] <Other Embodiments> The technology disclosed herein has been explained using positive electrode 32 or positive electrode 232 as an example. However, the technology disclosed herein can also be implemented for the negative electrode. In this case, the decrease in conductivity at the negative electrode is reduced. Furthermore, since the amount of copper at the negative electrode can be reduced, the weight of the negative electrode can be reduced, and consequently, the energy storage device can be miniaturized. When the technology disclosed herein is implemented at the negative electrode, the first metal powder and the second metal powder may be gold powder, silver powder, or copper powder.
[0088] In the embodiments described above, an electrode body 30 having a zigzag structure was described. However, the technology disclosed herein is not limited thereto. A laminated electrode body may be used instead of the electrode body 30. In a laminated electrode body, for example, a rectangular sheet-shaped positive electrode 32 or positive electrode 232 and a rectangular sheet-shaped negative electrode 34 are laminated with a rectangular sheet-shaped separator interposed between them.
[0089] The technologies disclosed herein may include the technologies described in the following sections. Section 1: A method for manufacturing an electrode comprising an electrode active material layer containing an electrode active material and a resin binder, and a current collecting layer provided on the surface of the electrode active material layer, The electrode active material layer is provided on the surface of the substrate, A slurry containing a first metal powder with an average particle size of less than 100 nm, determined by dynamic light scattering, is applied to the surface of the electrode active material layer provided on the substrate. The electrode active material layer and the slurry applied to the surface of the electrode active material layer are heat-treated at a temperature lower than the thermal decomposition temperature of the resin binder, thereby providing the current collecting layer on the surface of the electrode active material layer. to include, Manufacturing method. Section 2: The temperature of the heat treatment is 200 degrees or less. The manufacturing method described in item 1. Section 3: The aforementioned resin binder includes PVdF, The manufacturing method described in item 1 or 2. Section 4: In the application of the slurry, the slurry is applied to the surface of the electrode active material layer in a mesh shape. The manufacturing method described in any one of items 1 to 3. Section 5: The slurry further contains a second metal powder with an average particle size of 100 nm to 10 μm, determined by laser diffraction and scattering method. The manufacturing method described in any one of items 1 to 4. Item 6: The current collector layer includes air gaps, The manufacturing method described in any one of items 1 to 5. Section 7: The aforementioned second metal powder is composed of flake-shaped second metal particles. The manufacturing method described in any one of items 1 to 5. Section 8: The first metal powder and the second metal powder are of the same type of metal. The manufacturing method described in any one of items 1 to 7. Section 9: The electrode is the positive electrode. The manufacturing method described in any one of items 1 to 8. Section 10: The first metal powder is gold powder or silver powder. The manufacturing method described in any one of items 1 to 9. Section 11: A method for manufacturing an energy storage device including electrodes, The process includes manufacturing the electrode using the manufacturing method described in any one of items 1 to 10. Manufacturing method. Section 12: An electrode comprising an electrode active material layer containing an electrode active material and a resin binder, and a current collecting layer provided on the surface of the electrode active material layer, The aforementioned current collector layer is Metal particles having an average particle diameter of 100 nm to 10 μm based on electron microscope images of a cross-section along the thickness direction of the electrode active material layer, A metal bonding portion that connects the aforementioned metal particles, including, electrode. Section 13: The aforementioned metal bonding portion is molten metal. The electrode described in item 12. Section 14: The current collector layer includes air gaps, The electrode described in item 12 or 13. Section 15: The metal particles are in the form of flakes. An electrode as described in any one of items 12 to 14. Section 16: The metal particles and the metal bonding portion are of the same type of metal. An electrode as described in any one of items 12 to 15. Section 17: The current collector layer has a mesh shape in a plan view. An electrode as described in any one of items 12 to 16. Section 18: The electrode is the positive electrode. An electrode as described in any one of items 12 to 17. Section 19: The metal particles and the metal bonding portion are made of gold or silver. An electrode as described in any one of items 12 to 18. Section 20: A storage device comprising an electrode as described in any one of items 12 to 19. [Explanation of Symbols]
[0090] S base material 32,232 Positive electrode 32a,232a Positive electrode active material layer 32b,232b Positive electrode current collecting layer 91 Metal particles 92 Metal joints 1. Energy storage device
Claims
1. A method for manufacturing an electrode comprising an electrode active material layer containing an electrode active material and a resin binder, and a current collecting layer provided on the surface of the electrode active material layer, The electrode active material layer is provided on the surface of the substrate, A slurry containing a first metal powder with an average particle size of less than 100 nm, determined by dynamic light scattering, is applied to the surface of the electrode active material layer provided on the substrate. The electrode active material layer and the slurry applied to the surface of the electrode active material layer are heat-treated at a temperature lower than the thermal decomposition temperature of the resin binder, thereby providing the current collecting layer on the surface of the electrode active material layer. to include, Manufacturing method.
2. The temperature of the heat treatment is 200 degrees or less. The manufacturing method according to claim 1.
3. The aforementioned resin binder includes PVdF, The manufacturing method according to claim 2.
4. In the application of the slurry, the slurry is applied to the surface of the electrode active material layer in a mesh shape. The manufacturing method according to claim 1.
5. The slurry further comprises a second metal powder having an average particle size of 100 nm to 10 μm based on laser diffraction and scattering methods. The manufacturing method according to claim 1.
6. The current collector layer includes air gaps, The manufacturing method according to claim 5.
7. The aforementioned second metal powder is composed of flake-shaped second metal particles. The manufacturing method according to claim 5.
8. The first metal powder and the second metal powder are of the same type of metal. The manufacturing method according to claim 5.
9. The electrode is the positive electrode. The manufacturing method according to claim 1.
10. The first metal powder is gold powder or silver powder. The manufacturing method according to claim 9.
11. A method for manufacturing an energy storage device including electrodes, The electrode is manufactured using the manufacturing method described in any one of claims 1 to 10. Manufacturing method.
12. An electrode comprising an electrode active material layer containing an electrode active material and a resin binder, and a current collecting layer provided on the surface of the electrode active material layer, The aforementioned current collector layer is Metal particles having an average particle diameter of 100 nm to 10 μm based on electron microscope observation images of a cross-section along the thickness direction of the electrode active material layer, A metal bonding portion that connects the aforementioned metal particles, including, electrode.
13. The aforementioned metal bonding portion is molten metal. The electrode according to claim 12.
14. The current collector layer includes air gaps, The electrode according to claim 12.
15. The metal particles are in the form of flakes. The electrode according to claim 12.
16. The metal particles and the metal bonding portion are of the same type of metal. The electrode according to claim 12.
17. The current collector layer has a mesh shape in a plan view. The electrode according to claim 12.
18. The electrode is the positive electrode. The electrode according to claim 12.
19. The metal particles and the metal bonding portion are made of gold or silver. The electrode according to claim 18.
20. A power storage device comprising an electrode according to any one of claims 12 to 19.
Citation Information
Patent Citations
Positive electrode member, nonaqueous electrolyte battery, and method of manufacturing positive electrode member
JP2010170972A
All-solid lithium ion secondary battery
JP2015220107A
Power-storage component, secondary battery, electric double layer capacitor, ink jet printer and manufacturing method
JP2019164957A